Does the whistling thorn acacia (Acacia drepanolobium) use auditory aposematism to deter mammalian herbivores?. (2nd August 2016) - Lev-Yadun, Simcha
ABSTRACT: Auditory signaling including aposematism characterizes many terrestrial animals. Auditory aposematism by which certain animals use auditory aposematic signals to fend off enemies is well known for instance in rattlesnakes. Auditory signaling by plants toward animals and other plants is an emerging area of plant biology that still suffers from limited amount of solid data. Here I propose that auditory aposematism operates in the African whistling thorn acacia ( Acacia drepanolobium = Vachellia drepanolobium ). In this tree, the large and hollow thorn bases whistle when wind blows. This type of aposematism compliments the well-known conspicuous thorn and mutualistic ant based aposematism during day and may operate during night when the conspicuous thorns are invisible.